2015
DOI: 10.1308/003588414x14055925060235
|View full text |Cite
|
Sign up to set email alerts
|

A clinical conundrum with a radiological answer

Abstract: An 82-year-old woman with longstanding medial thigh pain presented with a 5-day history of constipation, vomiting, abdominal pain and distension. She was unable to pass flatus for the preceding 24 hours and had a past history of laparoscopic abdominal surgery. Computed tomography of the abdomen and pelvis revealed a right-sided obturator hernia containing a dilated loop of small bowel. She underwent emergency surgery for a right obturator hernia repair by limited laparotomy and was discharged after an extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…An obturator hernia is a relatively rare finding, accounting for 0.2%–1.6% of cases of mechanical intestinal obstruction 1 2. Recent studies have shown a higher incidence of 6% and suggested that the true incidence maybe higher if more patients underwent radiological evaluation prior to definitive management 3. Obturator hernias have a female predisposition with one study quoting an 1:16 male to female ratio 4.…”
Section: Descriptionmentioning
confidence: 99%
“…An obturator hernia is a relatively rare finding, accounting for 0.2%–1.6% of cases of mechanical intestinal obstruction 1 2. Recent studies have shown a higher incidence of 6% and suggested that the true incidence maybe higher if more patients underwent radiological evaluation prior to definitive management 3. Obturator hernias have a female predisposition with one study quoting an 1:16 male to female ratio 4.…”
Section: Descriptionmentioning
confidence: 99%